Physical Characteristics Analysis on Intelligent Reflecting Surface for High Speed Telecommunication Networks - Su Win, Naw Aye Myat Su; Tun, Hla Myo; Win, Lei Lei Yin; Win, Thanda; Aye, Mya Mya; Win, Khin Kyu Kyu; Soe, Khaing Thandar; Pradhan, Devasis (The Indonesian Institute of Science and Technology Research, 2025)
The paper mainly focuses on the physical characteristics analysis of an intelligent reflecting surface for high-speed telecommunication networks. The research problem in this study are (i) To overcome the bottleneck, a novel transmission scheme, named hybrid reflection modulation (HRM) must be considered, exploiting both active and passive reflecting elements at the RIS and their combinations, which enables to convey information without using any radio frequency (RF) chains, (ii) In the HRM scheme, the active reflecting elements using additional power amplifiers can be able to amplify and reflect the incoming signal, while the remaining passive elements can reflect the signals with appropriate phase shifts, (iii) Based on this novel transmission model, we will observe an upper bound for the average bit error probability (ABEP), and derive achievable rate of the system using an information theoretic approach, and (iv) Moreover, comprehensive computer simulations could be performed to prove the superiority of the proposed HRM scheme over existing fully passive, fully active and reflection modulation (RM) systems. The research directions are as follows: (i) Implementing the Intelligent Reflecting Surfaces (IRS) and Hybrid Reflection Modulation Technologies for 6G Wireless Communication, (ii) Implementing the Intelligent Reflecting Surfaces (IRS) and Hybrid Reflection Modulation Technologies with physical layer security techniques, and (iii) Modelling the mathematical equation for optimization design of IRS system. There are two portions in this study. The first is designing the signal model in the IRS surface with specific physical parameters. The second one is an analysis of the capacity of point-to-point MIMO channels. The analyses are conducted using by MATLAB language. The results confirm the performance specification of the IRS system for high-speed telecommunication applications.